A century of climate warming results in growing season extension: Delayed autumn leaf phenology in north central North America - Calinger, Kellen; Curtis, Peter (PLOS ONE, 2023)
Shifts in the timing of key leaf phenological events including budburst, foliage coloration, and leaf fall have been observed worldwide and are consistent with climate warming. Quantifying changes in growing season length (GSL) because of shifts in both spring and autumn leaf phenology is crucial for modeling annual net ecosystem carbon uptake. However, a lack of long-term autumn phenology datasets has prevented assessment of these growing season level changes. We investigated shifts in growing season length, budburst, foliage coloration, and leaf fall over the past century in seven native hardwood species using a historic leaf phenology dataset collected in Wauseon, OH from 1883–1912 paired with contemporary observations. Using long-term meteorological data, we investigated temperature and precipitation trends over 130 years. Finally, we correlated spring and fall phenophases with monthly temperature and precipitation variables from the twelve months preceding that phenophase using historical meteorological data. We found significant extension of growing season length over the past century in five of the seven study species (ANOVA, p < 0.05) which resulted primarily from delayed foliage coloration rather than from earlier budburst in contrast to the few other studies assessing total GSL change. Our results suggest that most of the leaf phenological studies that investigate only budburst are disregarding crucial information about the end of the growing season that is essential for accurately predicting the effects of climate change in mixed-species temperate deciduous forests.